2005
DOI: 10.1007/s11270-005-2249-7
|View full text |Cite
|
Sign up to set email alerts
|

A Lysimeter Study to Investigate the Effect of Dairy Effluent and Urea on Cattle Urine n Losses, Plant Uptake and Soil Retention

Abstract: Loss of nitrate (NO − 3 ) from grazing land is a major cause of surface and groundwater contamination. These losses increase when N sources such as fertilizer are applied to grazing land. The objectives of this work were to (1) study the impact of dairy effluent (DE) or urea on N losses and plant uptake when DE or urea was applied with and without cattle urine and; (2) determine the effect of organic C rich DE on the fate of urine N. The experiment was conducted using lysimeters that contained Templeton sandy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…Previous studies on urine-N fate in temperate environments have recorded similar lag periods of 1-3 months (Clough et al, 1996;Silva et al, 1999;Di and Cameron, 2007). The peak concentration of NO 3 À -N under autumn applied urine in other pasture based lysimeter studies has ranged from 50 to 225 mg N L À1 (Di et al, 2002;Decau et al, 2003;Silva et al, 2005;Di and Cameron, 2007) and the peak NO 3 À -N concentrations observed under autumn urine treatments in the current study are of a similar magnitude. Table 6 Percentage fertiliser recovered as 15 N from pasture, leachate, roots, stubble and soil fractions in lysimeters at the end of the study (28 August Significance of variation presented as: *P < 0.05; **P < 0.01; ***P < 0.001, n.s: not significant P > 0.05).…”
Section: Seasonal Effects On N Leachedsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies on urine-N fate in temperate environments have recorded similar lag periods of 1-3 months (Clough et al, 1996;Silva et al, 1999;Di and Cameron, 2007). The peak concentration of NO 3 À -N under autumn applied urine in other pasture based lysimeter studies has ranged from 50 to 225 mg N L À1 (Di et al, 2002;Decau et al, 2003;Silva et al, 2005;Di and Cameron, 2007) and the peak NO 3 À -N concentrations observed under autumn urine treatments in the current study are of a similar magnitude. Table 6 Percentage fertiliser recovered as 15 N from pasture, leachate, roots, stubble and soil fractions in lysimeters at the end of the study (28 August Significance of variation presented as: *P < 0.05; **P < 0.01; ***P < 0.001, n.s: not significant P > 0.05).…”
Section: Seasonal Effects On N Leachedsupporting
confidence: 81%
“…Decau et al (2004), Silva et al (2005), Leterme et al (2003) and Silva et al (1999)), this is one of the first studies to specifically partition the fertiliser component of the urine patchfertiliser combination to determine its effect on NO 3 À -N leaching. There was little variation in drainage between the lysimeters until spring 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2005) measured more N leaching from a urine patch that received 400 kg N ha À1 as fertilizer over a year than from urine alone. Using 15 N-labeled fertilizer, Buckthought (2014) suggested that additional N leaching was not necessarily fertilizer N, but a substitution in drainage by urinary N for the added fertilizer.…”
Section: Rate Of Urine N Applicationmentioning
confidence: 99%
“…During the dry season, DON could explain 58% variability of Chl-a concentration in the lagoon, which showed the relative importance of regenerated DON over anthropogenic DON to the primary producer when DIN:DIP was <16. Our present understanding of the linkages between nitrate, ammonium and urea fertilization and their transport to downstream aquatic systems is limited (Silva et al 2005;Di and Cameron 2008). The influence of in situ biogeochemical processes like DNRA, denitrification, mineralization, etc.…”
Section: Resultsmentioning
confidence: 99%